Methods for assessing the effectiveness of civil employees - Sinkevich K. V. (Scientific research and developments of students, 2016)
the article considers methods evaluating the performance of civil servants. In today's world, functioning of civil service efficiency is not possible without the participation of public servants, achieved goals and objectives of public authorities. Basically, the result of their activity depends on their own interest in the qualitative performance of official duties, the ability to take the initiative and apply professional knowledge and skills.
Keywords: государственное управление; public administration; госслужащий; метод оценки госслужащего; public employee; public employee evaluation method